Strategies for working with texts at the university (Research, Society and Development, 2020)
The use of texts as a didactic strategy in different curricular components in undergraduate courses is very common. In the teaching plans, on the date referring to the class, the teachers often only cite the reference of the text that will be used in certain classes. This strategy seems to imply the 'obviousness' of the learning objectives they want to achieve. However, due to the problems in the learning indicators, in the different teaching modalities in Brazil, evidenced in several national and foreign evaluations, and, relating to the persistent use of this strategy in Higher Education, we decided to research the theme in order to highlight the perceptions of students of Pedagogy courses on the use of didactic strategy based on reading academic texts. Our initial hypothesis is that there are problems in the teaching and learning processes resulting from the frequent and wrong use of this strategy, which could be better explored. The study methodology was based on a quantitative, qualitative / descriptive / interpretive / explanatory / comprehensive approach, recognizing the complex nature of reality. The study subjects were students entering Pedagogy courses at two institutions of Higher Education. The partial conclusions are that students find it difficult to assign meaning to this strategy; who find difficulties in reading; who are rarely able to read the required texts. The reasons evidenced are articulated with the profile of Pedagogy students, who enter the courses with important gaps in prior knowledge and with the way the didactic strategy is proposed. As suggestions to overcome this challenge, in the final referrals of the text, some alternative solutions were presented.